2018
DOI: 10.5897/ijlp2017.0392
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of factors affecting adoption of exotic chicken breed production in North Western Zone of Tigray, Ethiopia

Abstract: Exotic chicken breeds were promoted and disseminated in the rural and peri-urban parts of Ethiopia, to improve the productivity of the poultry to increase the income of farmers. The study was conducted to explore the factors affecting adoption of exotic chicken breed in Tselemti and Tahtay Koraro districts of North Western zone of Tigray region, Ethiopia. A multi-stage random sampling technique was followed to select 264 respondents from the six randomly selected Kebelles of the two districts. Primary data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…There was no ad-libitum (always) supplementation practice due to the absence of intensive poultry production. In agreement with Teklemariam (2017), the chicken keepers provided supplementary feed to all groups of age together three times per day (59.1%), twice per day (17%) and once per day (18.6%) and as the report of Nigatu and Bezabih (2014) stated, the chicken keepers in the area supplemented their chicken once, twice and more than twice per day 56.7%, 34.4% and 8.9 %, respectively. Grain feed provision (77.9%) was the most dominating feeding form and the habit of feed processing for supplementation was not commonly used practice in the study districts unless there were chicks that couldn't feed row grains.…”
Section: Chicken Production Practicementioning
confidence: 76%
See 4 more Smart Citations
“…There was no ad-libitum (always) supplementation practice due to the absence of intensive poultry production. In agreement with Teklemariam (2017), the chicken keepers provided supplementary feed to all groups of age together three times per day (59.1%), twice per day (17%) and once per day (18.6%) and as the report of Nigatu and Bezabih (2014) stated, the chicken keepers in the area supplemented their chicken once, twice and more than twice per day 56.7%, 34.4% and 8.9 %, respectively. Grain feed provision (77.9%) was the most dominating feeding form and the habit of feed processing for supplementation was not commonly used practice in the study districts unless there were chicks that couldn't feed row grains.…”
Section: Chicken Production Practicementioning
confidence: 76%
“…Still, there is no distribution of Broiler (meat type) chicken breeds in the Malle and Jinka districts of the South Omo Zone. Likewise, the improved chicken breeds such as the Bovan Brown, Rhode Island Red, and Koekoek were the most common poultry breeds that disseminated in Northwestern zones of Tigray (Teklemariam, 2017). The same author also reported that currently, pure exotic breeds such as Rhode Island Red and White Leg Horns are not available in commercial markets of Ethiopia.…”
Section: Distribution Of Improved Breeds and Productive Performancementioning
confidence: 99%
See 3 more Smart Citations